A case report on discoid lupus erythematosus (Indian Journal of Case Reports, 2025)
Inflammatory plaques are a hallmark of discoid lupus erythematosus (DLE), a chronic cutaneous illness that can cause skin shrinkage and disfiguring scarring if left untreated. The best treatments, however, are not well supported by the available data. As of right now, no drugs have been authorized expressly to treat DLE. This uncommon ailment manifests as a crimson telangiectatic lesion in the oral cavity, surrounded by white patches in the mucous membrane. Occasionally, thick or thin white papillary radiating patterns are visible around the lesion as extremely thin lines. Here, we present a 24-year-old male patient with oral DLE.